2016
DOI: 10.1039/c6ta06405a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanoparticle-semiconductor composites for efficient solar water splitting

Abstract: Photoelectrochemical (PEC) water splitting is a promising technology that uses light absorbing semiconductors to convert solar energy directly into a chemical fuel (i.e., hydrogen). PEC water splitting has the potential to become a key technology in achieving a sustainable society, if high solar to fuel energy conversion efficiencies are obtained with earth abundant materials. This review article discusses recent developments and discoveries in the mechanisms by which the localized surface plasmon resonance (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 115 publications
1
118
0
Order By: Relevance
“…showed that hot electrons are involved in a number of oxidation reactions on plasmonic clusters of Ag nanocubes under low‐intensity visible light illumination. Many studies devoted to water splitting, hydrogen evolution and oxygen evolution were recently reported and reviewed …”
Section: Plasmonic Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…showed that hot electrons are involved in a number of oxidation reactions on plasmonic clusters of Ag nanocubes under low‐intensity visible light illumination. Many studies devoted to water splitting, hydrogen evolution and oxygen evolution were recently reported and reviewed …”
Section: Plasmonic Electrochemistrymentioning
confidence: 99%
“…Many studies devoted to water splitting, hydrogen evolution and oxygen evolution were recently reported [49][50][51][52] and reviewed. 53 Plasmonic substrates have a potential for triggering specific reactions based on hot-electron and hot-hole charge transfer reactions. From an electrochemical point of view, this means that plasmon-induced electrochemistry is likely to become an important research field.…”
Section: Plasmonic Electrochemistrymentioning
confidence: 99%
“…(5) or (6) For the photoelectrochemicalc atalytic water splitting, the photocurrent on the photoelectrode is normally used to evaluate the activityo fc atalytic water splitting reactions, which is similart od irectly measuring the amount of evolved H 2 and O 2 . If the amounts of evolved H 2 and O 2 are even less than the amount of the photocatalyst, the TON can help us to clarify whether the reactions proceed photocatalytically.T urnover number is determined by the number of reacted molecules to the number of active sites.…”
Section: Evaluation Of Photocatalytic Water Splittingmentioning
confidence: 99%
“…[4,5] To give ac ontextual background, we begin by briefly describing the main process of water splitting on semiconductors,a nd the evaluation criteria of photocatalytic water splitting. [4,5] To give ac ontextual background, we begin by briefly describing the main process of water splitting on semiconductors,a nd the evaluation criteria of photocatalytic water splitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation